Sponge Diversity at Pecaron Bay Situbondo Based on Macroscopic and Microscopic Observation - Setiawan, Edwin; Nurhayati, Awik Pudji Diah; Muzaki, Farid Kamal (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2009)
The sponge species diversity recruited insitu macroscopic observation i.e, underwater photograph for sponges species diversity and spicula microscopic examination for sponges order group specimens have been conducted at Pecaron Bay Situbondo. Seventeen sponges species have been identified out of twenty species. The microscopic examination showed that the Diactinal oxea types were dominant in our 13 samples whereas the monoactinal oxea and style were represented only with 7 samples. Moreover, diactinal type of spicula can be used as an order group of sponges species at Pecaron bay Situbondo.